English Reduplicative Loans in Bangla - Sarwar Morshed (Master Program in Linguistics, Diponegoro University, 2019)
This small-scale exploratory study attempts to trace and taxonomize English reduplicative loans used in Bangla. Reduplicatives are the products of the morphological process known as ‘reduplication’ i.e. doubling of a word, stem or root. For example, ‘ha ha’, ‘dilly dally’, ‘hocus pocus’ etc. Though reduplication interfaces with both phonology and morphology, it is customarily included in the latter component of linguistics. The prime purpose of this paper is to detect and classify the morphological products in the form of reduplicative loans to Bangla from the English language. For the detection of loan reduplicatives, lexicographic works have been consulted. Social media sites have also contributed to the corpus on which this research is based. Our corpus reveals that Bangla has two types of English-based reduplicative loans – unchanged and changed. The unchanged category includes onomatopoeic and baby-talk reduplicatives. The members of the changed category, on the other hand, undergo different morphological modifications. One visible feature of the changed reduplicatives is that they are not borrowed as direct reduplicatives – initially they are borrowed as a single lexical item and then reduplication is carried out following the morphological rules of Bangla. Numerically speaking, the changed reduplicatives far outnumber the unchanged reduplicatives. There are a few English-based reduplicative loans that have been assimilated into the fabric of Bangla language – these few words are so strongly Banglicized that their English identity is unrecognizable without the help of etymological dictionaries. Apart from this fully integrated small category, there exists another class of loan reduplicatives that has effaced some full, unalloyed, internally sourceable reduplicatives. These guest reduplicatives along with their host peers and pair members have been instrumental in seasoning, salting and peppering Bangla.